Interface and model reduction for efficient explicit simulations - a case study with nonlinear vehicle crash models. Issue 4 (3rd July 2016) - Fehr, Jörg; Holzwarth, Philip; Eberhard, Peter
ABSTRACT: This work presents an approach to save simulation time in explicit crash simulations of vehicles by applying model order reduction (MOR). The model of a kart frame is split into linear and nonlinear parts. The linear part is reduced with linear MOR techniques in MatMorembs. Optimal substructuring methods are used to calculate suitable reduced models which are exported to LS-DYNA. Afterwards, the model consisting of a linear reduced part and a nonlinear part is simulated in the online step. The plastic deformation of the kart frame as well as the accelerations of the driver calculated with various reduction and parameter settings are compared with the accelerations measured when the original, unreduced nonlinear model is simulated. For optimal simulation results, the large interface between the models needs to be approximated by suitable interface-reduction approaches. The novel contribution is the application of advanced interface-reduction techniques in nonlinear explicit crash simulations. Craig–Bampton and Gramian matrix-based-like techniques with global, local and no interface reduction are compared to find optimally reduced substructures in terms of approximation quality of the assembled system and computational effort. For the kart frame, the applicability of the method is proven by gaining a small simulation speed up which cannot be achieved with the standard reduction methods provided by LS-DYNA.